The relationship between HR practices and employee turnover intention / Nurul Syazreen Khairudin - Khairudin, Nurul Syazreen (Faculty of Business and Management, 2018)
Employee turnover intention is the crucial issue that the organisation should prevent. Employee turnover could affect the growth of organisation as organisation loss the talented and good employee. When the good employees and talented employees leave the organisation, this could higher the cost of the organisation by recruit new employee and trains them. However HR practices is considered by the employee to turnover. Therefore, in this research, the researcher aims to determine the relationship between human resources practices which are participation, performance appraisal and job security, and employee turnover intention. This study using quantitative research which researcher distributing the questionnaires to the employees in the organisation to collect the data. The sampling design was convenience sampling. The data was collected and analysed by using Statistical Package for the Social Sciences (SPSS) software. SPSS software is used to collate the data and give the statistical result. Based on the data collected, the researcher has found out that the HR practices have significantly related to the employee turnover intention in the GD Express Sdn. Bhd. main office. HR practices which include participation, performance appraisal and job security were negatively correlated with the employee turnover intention. This means that when HR practices were satisfying the employees, the employee will not have the intention to turnover.